The Saqqara Necropolis through the New Kingdom : Biography of an Ancient Egyptian Cultural Landscape - Staring, Nico, (Culture and History of the Ancient Near East ;, 2023)
This book is the first comprehensive monographic treatment of the New Kingdom (1539-1078 BCE) necropolis at Saqqara, the burial ground of the ancient Egyptian city of Memphis, and addresses questions fundamental to understanding the site's development through time. For example, why were certain areas of the necropolis selected for burial in certain time periods; what were the tombs' spatial relations to contemporaneous and older monuments; and what effect did earlier structures have on the positioning of tombs and structuring of the necropolis in later times? This study adopts landscape biography as a conceptual tool to study the long-time interaction between people and landscapes.